DECONSTRUCTED REALITY, TANGIBLE HARM: FROM ONLINE FAKE NEWS TO GENOCIDE - Nascimento, Bárbara Luiza Coutinho do (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2025)
This paper studies the historical development of the international crime of incitement to genocide, from its origins in Nuremberg to its contemporary online format, identifying the role of the media and fake news in it. Showing this progression and describing its underlying patterns is a research effort for legally interpreting a phenomenon. After identifying the elements of the crime according to international law and presenting the new aspects brought by cybercommunications, the paper analyses the Myanmar case to demonstrate how the existing legal framework may be applied to social media posts spreading fake news. Lastly, concerning speeches falling outside the scope of the norm, the paper proposes a new crime prohibiting the conduct of systematically creating or distributing fake news online when such conduct constitutes computational propaganda with the intent to harm groups protected under the Genocide Convention and assesses the democratic justification of the proposal.